Ultrasound-Guided Peripheral Nerve Blocks Performed by Orthopedic Surgeons: A Retrospective, Multicenter Study in Akita Prefecture, Japan. (10th March 2021) - Tomioka, Tatsuru; Senma, Seietsu; Narita, Yuichiro; Urayama, Masakazu; Yumoto, Satoshi; Ito, Hiroki; Aizawa, Toshiaki; Shirahata, Tsuyoshi; Aonuma, Hiroshi; Kaga, Nozomi; Masutani, Norimitsu; Yuasa, Yusuke; et al.
Abstract : The shortage of doctors is a societal problem, especially in rural areas such as Akita Prefecture, Japan. Therefore, it is not unusual in Akita for orthopedic surgeons to perform upper and lower limb surgeries under ultrasound-guided peripheral nerve blocks managed by the operators themselves. Multicenter studies of ultrasound-guided peripheral nerve blocks performed by orthopedic surgeons have not been reported. The purpose of this study was to clarify the safety and reliability of ultrasound-guided peripheral nerve blocks performed by orthopedic surgeons in Akita. A total of 1, 674 upper extremity surgery cases operated under ultrasound-guided peripheral nerve blocks at 8 hospitals in Akita prefecture from April 2016 to April 2018 were investigated retrospectively. These blocks were performed by a total of 37 orthopedic surgeons, including senior surgeons and residents. In 321 of the 1, 674 cases (19%), local anesthetics were added to the surgical field. Two cases with special factors were converted to general anesthesia. There were 2 cases of complications associated with the nerve block, but they were all transient and recovered promptly. The block site and the hospital where the block was performed showed a significant relationship with the addition of local anesthetics to the surgical site (P < 0.001 ). Surgery time, age at surgery, and surgical site showed no significant relationships with the addition of local anesthetics. The volume of the anesthetic used for the nerve block showed a significant inverse relationship with the addition of local anesthetics (P = 0.040 ). Many orthopedic surgeons in Akita prefecture began to perform ultrasound-guided peripheral nerve blocks, which had a reliable anesthesia effect with no noticeable complications, whether performed by residents or senior orthopedic surgeons, and this is a useful anesthetic technique for orthopedic surgeons.